Hydatidiform mole in the Maternity Hospital of San Bartlomé - Ludmir, Abraham (2015)
A 0.23% incidence of benign Hydatidiform Mole, comparable with similar groups of patients is found at the Hospital Materno Infantil de San Bartolomé in Lima. Most of the 13 cases reported occurred in young to middle-age women, parous three or more, although 30% were first pregnancies. The most common symptoms were vaginal bleeding (100%), vomiting, softness (46.1 %) and excessive growth of the uterus (61.5%). Toxemic symptoms were present in only 23% of the women. Evacuation was accomplish by oxytocin followed by curettage in 53.7% of the cases. In the remaining ones hysterotomy was necessary and a 30.7% incidence of lutein cysts was detected. A low incidence of complications, absence of malign transformation and of maternal death are reported.